1997
DOI: 10.1002/art.1780400912
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the HOX4C gene by basic fibroblast growth factor on rheumatoid synovial fibroblasts

Abstract: Objective. To examine the expression of genes of the HOX D cluster in the synovial tissue of patients with rheumatoid arthritis (RA), and to determine whether basic fibroblast growth factor (bFGF) influences the expression and transcriptional regulation of the gene.Methods. The expression of genes of the HOX D cluster, including HOX4C, HOX4D, HOX4H, and HOX41, was determined in the synovium of 4 patients with RA and 4 with osteoarthritis (OA) by in situ reverse transcription (RT) and RT-polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…We previously reported that HoxD9, one of the homeobox gene families which controls cell growth and pattern formation during embryogenesis, is overexpressed exclusively in rheumatoid synovium [23,24]. HoxD9 is a transcriptional factor that determines the planning of the body.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that HoxD9, one of the homeobox gene families which controls cell growth and pattern formation during embryogenesis, is overexpressed exclusively in rheumatoid synovium [23,24]. HoxD9 is a transcriptional factor that determines the planning of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Basic FGF, TNF␣, and TGF␤ are abundantly expressed in rheumatoid synovium, and are important cytokines involved in the regulation of cellular growth (4,5,32,33). Furthermore, bFGF and TGF␤ also activate the expression of several HOX genes (27,(34)(35)(36). Accordingly, we compared the effects of these cytokines on HOXD9 transcription in cotransfec- HOXD9 AND SYNOVIOCYTE PROLIFERATION tion assays in NIH3T3 fibroblasts and synoviocytes using a luciferase reporter construct carrying HCR, an autoregulatory element of HOXD9 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…However, very little is known about its function in normal and pathologic adult tissues. In a series of recent studies, we have demonstrated preferential expression and activation of HOX genes in the rheumatoid synovium of adult patients, indicating that these genes are involved in the pathogenesis of arthritis (27,28). We previously reported that HOXD9 mRNA was characteristically expressed in RA synovium (27), and in this study we provide additional evidence that HOXD9 protein was detected in cultured rheumatoid synoviocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations